1994
DOI: 10.1007/bf02348226
|View full text |Cite
|
Sign up to set email alerts
|

Electron microscopic and immunohistochemical studies of oral malignant melanoma

Abstract: Abstract.A rare variety of malignant melanoma in the maxilla was studied by electron microscopic observation and an immunohistochemical investigation of the transferrin receptor (TfR). A number of low-stage melanosomes were seen, and the TfR was found in both the cell membrane and the cytoplasm.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1998
1998
2002
2002

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…As indicated in Fig. 2, the complex 1 consists of three Os atoms that form an isosceles triangle with distances Os(1)-Os(2) ~2.9135(4), Os(1)-Os(3) ~2.8685(4) and Os(2)-Os(3) ~2.8642(4) A ˚, of which the longer Os-Os edge is bridged by the pyrazolate ligand and a hydride ligand at the opposite position, with distances Os(1)-H(1) ~1.79 (6) and Os(2)-H(1) ~1.80(6) A ˚. Basically, this structure can be considered to derive from the parent complex Os 3 (CO) 12 by replacement of two axial CO groups on adjacent Os atoms by the bridging pyrazolate and hydride ligands.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…As indicated in Fig. 2, the complex 1 consists of three Os atoms that form an isosceles triangle with distances Os(1)-Os(2) ~2.9135(4), Os(1)-Os(3) ~2.8685(4) and Os(2)-Os(3) ~2.8642(4) A ˚, of which the longer Os-Os edge is bridged by the pyrazolate ligand and a hydride ligand at the opposite position, with distances Os(1)-H(1) ~1.79 (6) and Os(2)-H(1) ~1.80(6) A ˚. Basically, this structure can be considered to derive from the parent complex Os 3 (CO) 12 by replacement of two axial CO groups on adjacent Os atoms by the bridging pyrazolate and hydride ligands.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
“…Since the first successful deposition of Os metal by hydrogen reduction of OsCl 4 vapor, 4 only a few reports have been focused on its continued improvement. In recent years, work on the chemical vapor deposition of osmium has started to utilize the commercially available osmocene (C 5 H 5 ) 2 Os, 5 osmium tetraoxide OsO 4 , 6 or even the metal carbonyl complexes such as Os(CO) 5 , 7 Os 3 (CO) 12 , 8 and Os(CO) 4 (hfb), 9,10 where hfb ~hexafluorobut-2-yne, to produce pure osmium metal or the respective metal oxide material OsO 2 . It has been reported that thin films with reasonable purity were obtained in most of the previous studies; however, the usage of these source reagents has encountered difficulties such as the greater toxicity of OsO 4 , poor thermal stability of Os(CO) 5 , and lower gas phase transportation capability for the osmocene complex (C 5 H 5 ) 2 Os and polynuclear metal complex Os 3 (CO) 12 .…”
mentioning
confidence: 99%